1976
DOI: 10.1136/bmj.1.6000.7
|View full text |Cite
|
Sign up to set email alerts
|

Jolly fat: relation between obesity and psychoneurosis in general population.

Abstract: SummaryThe relation between fatness and aspects of psychological status was investigated in a representative sample (339 men and 400 women) of a middle-aged suburban population. A significant positive relation was found between substantial obesity and low levels of anxiety (in men and women) and depression (in men).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
188
3
7

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(222 citation statements)
references
References 23 publications
24
188
3
7
Order By: Relevance
“…Studies support the possibility of depression promoting obesity and vice versa as association has been seen between the factors in several studies (Wadden et al, 1988(Wadden et al, , 1997Istvan et al, 1992;Sullivan et al, 1993;Faith et al, 2002), while older cross-sectional studies do not support this relation (Crisp & McGuinness, 1976;Stewart & Brook, 1983). Lower levels of cognitive stimulation, because of depression or low self-esteem among heavier mothers cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%
“…Studies support the possibility of depression promoting obesity and vice versa as association has been seen between the factors in several studies (Wadden et al, 1988(Wadden et al, , 1997Istvan et al, 1992;Sullivan et al, 1993;Faith et al, 2002), while older cross-sectional studies do not support this relation (Crisp & McGuinness, 1976;Stewart & Brook, 1983). Lower levels of cognitive stimulation, because of depression or low self-esteem among heavier mothers cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%
“…'The Jolly Fat' -hypothesis was presented in the 1970s, when a positive association was found between obesity and low levels of anxiety in men and women, and low levels of depression in men. 13 On the other hand, recent studies have mostly observed an increased risk for depression among the obese. 14,15 Most of the epidemiological studies concerning the association between obesity and depression have been cross-sectional.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22] However, other studies do not support this association, 14,15,17,23,24 and a few have even reported better mental health among people with excess body weight. [25][26][27][28] The discordant results from these studies may be due in part to methodological limitations. Most studies have examined patients seeking treatment for obesity, who tend to have more impaired HRQOL and more disturbances, such as eating disorders than those not seeking treatment.…”
Section: Introductionmentioning
confidence: 99%